Pain Assessment Documentation After Opioid Administration at a Community Teaching Hospital. (April 2019) - Phillips, Megan E.; Gilmore, Rod A.; Sheffield, Melody C.; Phan, Stephanie V.
Purpose: To compare pain assessment documentation postopioid administration in hospitalized patients before and after implementing nurse education. Methods: Patients 18 years and older were randomly selected for inclusion if they received 1 opioid dose while admitted to the hospital. Through retrospective chart review, opioid data, including date and time, were collected for each opioid administered. Pain score data, including time and date of documentation, were recorded for analysis. The primary objective of this study was to determine whether a nursing education intervention would improve documentation of pain scores within an appropriate time frame postadministration of an opioid medication. The intervention was a training presentation uploaded to the institution's intranet with an assessment. The primary outcome was measured by comparing the frequency by which nurses documented pain scores following opioid administration before and after education. Results: Three hundred twenty patients (160 patients per time period) were evaluated. The percentage of pain scores recorded within the appropriate assessment time following opioid administration increased from 32.9% to 37.8% ( P = .003). The proportion of appropriate pain score documentation increased 4.9% (95% confidence interval [CI]: 1.6%-8.2%). Conclusion: An increase in the documentation of efficacy assessments after opioid administration was demonstrated after nursing education. Further studies should be done to identify additional strategies to increase monitoring as well as to identify a benchmark for institutions with regard to pain management monitoring.